2009
DOI: 10.1515/jpem.2009.22.3.269
|View full text |Cite
|
Sign up to set email alerts
|

Activating TSH-Receptor Mutation (Met453Thr) as a Cause of Adenomatous Non-Autoimmune Hyperthyroidism in a 3 Year-old

Abstract: Several mutations of the TSH-receptor gene have been described in a variety of thyroid diseases. Particularly in children and adolescents, somatic or germ cell mutations may lead to hyperthyroidism. In these cases, molecular analysis of the TSHR gene provides important information for further clinical management. We report a 3-year-old boy with a rare somatic TSHR mutation causing autonomous adenoma of the thyroid gland in order to illustrate how the genetic analysis of the lesion impacted on the surgical stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…The T > C mutation in codon 453 of the TSH receptor gene found here was previously reported in the setting of nonautoimmune hyperthyroidism [32] but without any RUNX2, SALL1, or SAMD9 involvement. Wide tissue expression of TSHRs is well established, and includes brain, bone marrow, lymphocytes, pituitary, thymus, testes, kidney, adipose tissue, and broblasts [33].…”
Section: Discussionsupporting
confidence: 68%
“…The T > C mutation in codon 453 of the TSH receptor gene found here was previously reported in the setting of nonautoimmune hyperthyroidism [32] but without any RUNX2, SALL1, or SAMD9 involvement. Wide tissue expression of TSHRs is well established, and includes brain, bone marrow, lymphocytes, pituitary, thymus, testes, kidney, adipose tissue, and broblasts [33].…”
Section: Discussionsupporting
confidence: 68%
“…The novel mutation identified in this study is located at codon 458 (exon 10), close to a proven functional M453T TSHR transmembrane domain mutation, where most activating TSHR mutations occur (14,15). It was reported that an activating germline M453T TSHR mutation caused non-autoimmune hyperthyroidism (28,29).…”
Section: Discussionmentioning
confidence: 75%
“…This yielded 8 publications [2,12,13,14,15,16,17,18] describing 16 autonomous adenomas in which a somatic TSHR mutation had been documented in 14 patients younger than 18 years (1 patient had 3 autonomous adenomas). To these, we added 2 of our own unpublished patients, who are described in detail below.…”
Section: Methodsmentioning
confidence: 99%